Socialization of social media as a means of building peace culture among the z-generation in Samarinda City - Devy Indah Paramitha; Intan Kinanti Damarin Tyas (Universitas Muhammadiyah Magelang, 2022)
The development of modern era must be followed by the development of a mature mindset, especially the use of social media. Today, technological advances have implications for the easy flow of information from all social media platforms. However, this ease has triggered hate speech and led to cyber bullying in the community. On the other hand, social media is also often used as a tool to spread hoax news. Any information from social media must be used to prevent conflict. Therefore, this community service will be carried out as a preventive step to build public understanding of social media, so that it is hoped that social media will become a tool for a culture of peace. The activity is carried out by providing an understanding of how to use social media properly and wisely through the use of the TEPAR formula. The result of the program shows an increase in knowledge related to the use of social media as a means to create a peace culture.